Leadership, Professional Development and Higher Education Institutions: A Study of Constituent Campuses of Tribhuvan University - Dhakal, Bhakta Prasad (Myagdi Guru, 2024)
This article aims to explore the aspects of leadership at constituent campuses run under Tribhuvan University in Kathmandu Valley. For this, only five constituent campuses have been selected purposefully to analyze the factors of leadership, where selected participants using purposive sampling have been designated in accordance with their perspectives and personal experiences. In-depth interviews were developed to collect information from participants to comprehend their viewpoints about leadership and the working ability of different campuses. Throughout the interviews, we tried to comprehend the respondents’ explanations, experiences, observations, and evidence about leadership. The discussion was coded to generate themes in light of the key concepts of transformative leadership theory in order to reach a conclusion. The findings showed that effective leadership is influenced by a variety of factors, including the degree of interaction, problem-solving skills, collaboration, and decision-making capacity to develop the campuses academically, financially, and administratively. Leadership is detrimental to professional development, and the qualities of campuses are positively impacted by regular communication between faculty, staff, and stakeholders. The leadership was inspired to enhance organizational capacity and collaboration by the deft problem-solving skills of the lead instructor. The transformative leadership gives priority and sets values for the improvement of educational quality is the main aspect of this paper. The leadership has to be made more aware of this to achieve the goals of higher education in the twenty-first century, which are essential to upholding a high standard of cooperation while upholding the principles of efficient communication and teamwork.